Biological aspects of tambra fish (Tor tambroides Blkr.) that exotic and rare for its domestication (Biodiversitas Journal of Biological Diversity, 2006)
Tambra (Tor tambroides Blkr.) is consumed fish; its exotic size, rare population and expensive price but not yet cultured. The aims of study are to know biological aspects tambra fish, i.e: sexual maturity, fecundity, sexual dimorfism, sex ratio, food habits, parasities and dissease. The results were recorded two levels of sexual maturity that III and IV, fecundity ranges 3,125-8,201 eggs, sex ratio 1:2; sexual dimorfism based on shape and color body, tubercle at cheek and operculum of male, also papilla shape; food habits as omnivorous; founded two species of parasities, i.e. Argulus sp. and Lernea cypriniaceae. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: tambra fish, biology aspects, domestication, exotic, rare and expensive